2016
DOI: 10.1093/brain/aww054
|View full text |Cite
|
Sign up to set email alerts
|

High risk of cancer in autoimmune necrotizing myopathies: usefulness of myositis specific antibody

Abstract: Cancer can occur in patients with inflammatory myopathies. This association is mainly observed in dermatomyositis, and myositis-specific antibodies have allowed us to delineate patients at an increased risk. Malignancy is also reported in patients with necrotizing autoimmune myopathies, but the risk remains elusive. Anti-signal recognition particle or anti-HMGCR antibodies have been specifically associated with necrotizing autoimmune myopathies. We aimed at screening the incidence of cancer in necrotizing auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
4
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(173 citation statements)
references
References 16 publications
4
149
4
16
Order By: Relevance
“…Specifically, autoantibody-negative IMNM has been associated with a markedly increased risk of malignancy (95%SCR CI: 8.35–24.41) [30••]. In contrast, anti-HMGCR myopathy may have a relatively weak association with cancer (95%SCR CI: from 0.4–2.4 to 1.02–6.07) [30••], although this has not been demonstrated in all cohorts [21••, 31•, 32•, 33••]. Finally, anti-SRP myopathy is not associated with cancer [13••, 16••, 30••, 33••, 34•].…”
Section: Cancer Associationmentioning
confidence: 99%
“…Specifically, autoantibody-negative IMNM has been associated with a markedly increased risk of malignancy (95%SCR CI: 8.35–24.41) [30••]. In contrast, anti-HMGCR myopathy may have a relatively weak association with cancer (95%SCR CI: from 0.4–2.4 to 1.02–6.07) [30••], although this has not been demonstrated in all cohorts [21••, 31•, 32•, 33••]. Finally, anti-SRP myopathy is not associated with cancer [13••, 16••, 30••, 33••, 34•].…”
Section: Cancer Associationmentioning
confidence: 99%
“…A recent study of 115 patients identified malignancy in 17.3% in the anti-HMGCR cohort, with lung, breast, renal, oesophagus, gastric, ovarian and endometrial cancers detected 6. We typically perform whole-body fluorodeoxyglucose positron emission tomography-CT imaging, with or without gastrointestinal endoscopy, with testicular ultrasound in men and mammograms in women.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, they have been found in association with immune-mediated necrotising myopathies in patients who have never been exposed to statins, including children. Furthermore, there is mounting evidence of an increased incidence of cancer in people with HMGCR related immune-mediated necrotising myopathy, with or without a history of statin exposure 32. This needs further study, but on current evidence, it seems reasonable practice to consider the possibility of underlying malignancy in adults presenting with immune-mediated necrotising myopathy with HMGCR antibodies, as one should do with patients presenting with dermatomyositis.…”
Section: Statin-related Myopathiesmentioning
confidence: 99%